Mega-City-Regions: on Awareness and Value Chain Approach - Michael Dross; Agnes Forster; Alain Thierstein (European Regional Science Association (ERSA), 2006)
Mega-City-Regions (MCR) as a new large-scale urban phenomenon have been gaining attention recently: In research, empirical studies address their functional consistency, and spatial planning policies underline the strategic role of MCRs for territorial competition of a country. But increasingly a tension between the functional logic of knowledge-intensive business activities and the territorial and normative approaches of public bodies begin to emerge. Typical conflicts of spatial development in MCRs occur for example when globally motivated investment decisions hit upon the local needs. This paper proposes an integrated view that can help to bridge the gap between the growing factual knowledge about MCRs and the still weak ability to use this knowledge for local and regional development and spatial planning purposes. The proposed integration draws on the one hand from the corporate-based value chain approach: The interaction of analysis of spatio-economic development, its adequate visualization and focussed communication towards stakeholders is apt to bring about the initiating momentum for beneficial spatial development. In the context of a diffuse perception of MCRs – whose mere size surpasses our common notions of space – analysis, visualization and communication as methodological components in the spatial planning process add value to sustainable spatial development. The process starts with creating awareness for the often invisible and complex functions, qualities and identities of the MCR spatial scale. New strategies of visualization and communication are needed to improve insight and motivation of the actors involved. On the other hand this value chain approach has to be adapted to the varying vertical levels of public bodies with their numerous policies. Thus, "multi-level-governance" is to be conceived as a concept to close the gap between the territorial and the functional logic of spatial development. The paper will study this dual approach with the case of the announced expansion of the international airport in Munich. This complex multi-level-governance process experiments with a consensus-oriented dialogue platform – the so called "neighbourhood conference" (NC) – bringing together actors with divers responsibilities and objectives. The NC sits at the interface of global and local objectives that are transformed on the spatial scale of the MCR of Munich. The paper concludes with recommendations for using the above described spatial value chain approach for more efficient multi-level-governance.
Keywords: 330